Optimisation approach for pollution source identification in groundwater: an overview. (28th June 2011) - Chadalavada, Sreenivasulu; Datta, Bithin; Naidu, Ravi
Groundwater pollution occurs from different anthropogenic sources like leakage from Underground Storage Tanks (USTs) and depositories, leakage from hazardous waste dump sites and soak pits. Remediation of these contaminated sites requires optimal decision-making system so that the remediation is done in a cost-effective and efficient manner. Identification of unknown pollution sources plays an important role in remediation and containment of contaminant plume in a hazardous site. This paper reviews different optimisation algorithms like classical, nonclassical such as Genetic Algorithm, Artificial Neural Network and Simulated Annealing and hybrid methods, which can be applied for optimal identification of unknown groundwater pollution sources.